El desarrollo psicomotor y el juego en los jóvenes con discapacidad intelectual, “CEPRODIS”, Loja, periodo 2014 - Sedamanos Poma, Diego Fabian (2015)
The theme of our research is the psychomotor development and play in young people with intellectual disabilities, CEPRODIS Loja period 2014. The improved psychomotor skills and capacities of individuals, when used with the matching results are effective in young people with intellectual disabilities, so the problem that arises is how to contribute to a set of playful for psychomotor and intellectual development of young male and female between the ages of 14 to 30 games in "CEPRODIS" in the period 2014 ?, the proposed objective was to evaluate the recreational activities as part of psychomotor development (CEPRODIS) in relation to intellectual problem of youth, in the period 2014, the methodology is done through methods such as scientific, empirical, observational, analytical, inductive, deductive and statistical method has a quantitative approach because mathematical and statistical processes are used to process data from surveys and tests performed using the technique of the survey to parents determine the degree of disability and plan fun activities to develop motor skills of young people, with an assessment test to measure psychomotor development, the results of this investigation indicate that, psychomotor difficulties presented youth decrease with game application, these results oriented to make some conclusions as insufficient motor coordination, balance and strength, followed by the lack of stimulation of attention, memory, communication and language, also directed to the realization and implementation of some recommendations how; institutions that manage youth with intellectual disabilities organize integration programs with fun activities to improve disability.